EFFECT OF TREATMENT WITH TRICHODERMA SPP ON THE LEVEL OF PEROXIDASE, POLYPHENOLOXIDAES AND CHITINASE IN COWPEA PLANTS VIGNA UNGUICULATA EFFECTED BY ROOT-KNOT NEMATODAS MELOIDOYGNE JAVANICA - aAsmaa Abdul-rasool (Mesopotamia Journal of Agriculture)
Two isolates of biocontrol agent Trichoderma spp involved a mutant isolate Trichoderma harzianum Thk20 and Trichoderma viride were used in this study Results revealed the ability of two isolates in inducing systemic disease resistance in cowpea plants against root knot nematode Meloidogyne javanica throughout increasing the activity of peroxidase, polyphenoloxidas and chitinase enzymes in cowpea roots. Isolates Thk20 caused highest activity of peroxidase 1.83 unit/g f.w. and polyphenoloxidase 5.58 unit / g f.w comparing with other treatments, at the same time this isolate did not differ significantly with the other isolate and the treatment (M. javanica + T. viride) where enzyme activity were 5.12 and 5.21 unit / g f.w respectively . The treatment (M. javanica + Thk20) caused the highest activity of chitinase enzyme in cowpea roots with 10.74 unit / g f.w followed by (M. javanica +T. viride), Thk20 and T. viride in which enzyme activity was 7.45, 5.34 and 5.23 unit / g f.w respectively.